Sejarah kejururawatan dari perspektif Islam: satu kajian perpustakaan - Mohamad Firdaus, Mohamad Ismail; Norazmi, Anas; Siti Zuhaidah, Shahadan (Pusat Pembangunan Penyelidikan, Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2021)
The nursing career is a glorious career that is likened to the lifeblood of the medical world. Without the existence and role of nurses in the world, especially in hospitals, then the health system is paralyzed. The history of nursing is heavily influenced by Western philosophy and it is very difficult to see the spirit of Islam in that aspect. Therefore, the objective of this study will be to fill the void with an exploration of the elements of nursing in Islamic history. Library research is used to obtain information with a descriptive, analytical and thematic content analysis approach. The results of the study found that elements of nursing such as helping patients ’daily activities and reducing patients’ suffering have long been practiced since prophetic times, even though they were not called nurses at the time. Many Muslim nursing figures emerged during the time of the Prophet Muhammad as a Messenger. Rufaidah Saad al-Aslami is a Muslim nursing figure who has made many innovations in patient care so that the Western world has also taken inspiration and lessons from her career journey. Therefore, the findings of this study are expected to open the eyes of society that the history of Islam has contributed a lot in the evolution of nursing from ancient times to modern times. With the application of Islamic history in nursing, Muslim nurses will be more confident and appreciate the practice of nursing as a wasilah to seek the pleasure of Allah.